2021
DOI: 10.3390/ijms222010972
|View full text |Cite
|
Sign up to set email alerts
|

Palmitic Acid-Induced miR-429-3p Impairs Myoblast Differentiation by Downregulating CFL2

Abstract: MicroRNAs are known to play a critical role in skeletal myogenesis and maintenance, and cofilin-2 (CFL2) is necessary for actin cytoskeleton dynamics and myogenic differentiation. Nonetheless, target molecules and the modes of action of miRNAs, especially those responsible for the inhibitory mechanism on the myogenesis by saturated fatty acids (SFA) or obesity, still remain unclear. Here, we reported the role played by miR-429-3p on CFL2 expression, actin filament dynamics, myoblast proliferation, and myogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
(84 reference statements)
1
7
0
Order By: Relevance
“…Several studies have examined the direct effects of PA on cultured myoblasts and myocytes. Similar to the findings of the present study, treatment of myoblasts with PA has been shown to inhibit myogenic cell differentiation and myotube maturation [ 21 , 22 , 39 , 40 ] and reduce type II myosin protein expression [ 41 ]. We further clarified the detailed mechanism by which PA treatment selectively inhibits the expression of specific MHC isoforms at a transcription level during myoblast differentiation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Several studies have examined the direct effects of PA on cultured myoblasts and myocytes. Similar to the findings of the present study, treatment of myoblasts with PA has been shown to inhibit myogenic cell differentiation and myotube maturation [ 21 , 22 , 39 , 40 ] and reduce type II myosin protein expression [ 41 ]. We further clarified the detailed mechanism by which PA treatment selectively inhibits the expression of specific MHC isoforms at a transcription level during myoblast differentiation.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, PA has been shown to induce endoplasmic reticulum (ER) stress, which in turn triggers programmed cell death via apoptosis [ 19 , 20 ]. PA also regulates the expression of several microRNAs, thereby inhibiting myoblast differentiation and maturation into myofibers [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Defects in myoblast functions can result in a loss of muscle mass and decline in performance, which are characteristics of patients with sarcopenia. The immortalized murine cell line C2C12 or transformed rat cell line L6 is commonly utilized to study the regulation of metabolism and myogenesis in skeletal muscle cells [ 9 , 10 , 11 , 12 , 25 , 26 , 27 ]. Few studies have utilized in vitro differentiated human myotubes obtained by long-term maintenance of human myoblasts from multiple donors in the presence of recombinant growth hormones [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of miRNA sequencing, it was observed that miR-429-3p was highly expressed in a high fat chickens. Furthermore, Nguyen et al [74] examined the role of miR-429-3p on myoblast proliferation and myogenic differentiation in their experiment.…”
Section: Discussionmentioning
confidence: 99%